Activating Prior Knowledge through KWL Strategy in Young EFL Learners’ Reading - Rozy, Fianico Sukmana (Journal of Early Childhood Education Studies, 2025)
The KWL strategy (Know, Want to know, Learned) is a pedagogical approach designed to activate prior knowledge and enhance reading comprehension, particularly effective for young learners of English as a Foreign Language (EFL) aged 7 to 12 years. This strategy supports cognitive and metacognitive development by guiding students to reflect on their existing knowledge, generate questions based on their learning needs, and consolidate newly acquired information. It addresses the linguistic and cognitive challenges young EFL learners face by reducing cognitive load and fostering active engagement with reading materials. The flexibility of KWL allows educators to adapt it using visuals, simplified language, and collaborative activities, making it suitable for diverse multilingual classroom settings. Empirical research demonstrates that KWL improves learners’ retention, organization of ideas, critical thinking, and motivation. Effective teacher facilitation, including explicit modeling and scaffolding, is essential to maximize the strategy’s benefits. Moreover, KWL promotes social interaction and cultural responsiveness, which further supports language acquisition and learner confidence. Overall, the KWL strategy offers a systematic, learner-centered framework that nurtures autonomous and motivated readers, contributing significantly to the development of reading comprehension skills in young EFL learners.